PERILAKU PENGGEMAR K-POP DAN K-DRAMA PADA SISWA SMA/MA DI KOTA MATARAM - Dayu Irmasuci; Ni Made Novi Suryanti; Nursaptini Nursaptini; Masyhuri Masyhuri (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2025)
The purpose of this research is to understand the behavior of high school K-Pop and K-Drama fans in Mataram city and to examine the impact of K-Pop and K-Drama on these students' behavior. This study uses a qualitative method with a phenomenological approach. Data collection techniques include observation, semi-structured interviews, and documentation. The study involves nine main subjects and two informants, selected based on their status as fans of the Korean Wave or K-Pop. The findings indicate that the behavior of high school K-pop and K-drama fans in Mataram city is evident in a) the knowledge domain, where students watch and observe their idols both directly and indirectly through social media or television; b) the attitude domain, where students admire actors, actresses, or idol groups and follow their idols' activities, feeling motivated to emulate their idols and adopting their personalities; c) the skills domain, where students use Korean language phrases, dress in Korean-inspired fashion, and participate in Korean events and communities.